Shielding characteristics of composite materials based on titanium dioxide and gypsum - O. V. Boiprav; N. A. Neverov; N. V. Bogush; L. M. Lynkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Electromagnetic radiation reflection and transmission characteristics of composite materials obtained by forming into a plate a mixture based on powdered titanium dioxide and a gypsum binder were studied, depending on the thickness of these materials. According to the research results, approaches to the practical use of studied materials in electromagnetic shielding systems were developed.